Patient-reported outcome measures for monitoring primary care patients with depression: PROMDEP feasibility randomised trial. Issue 3 (30th March 2017) - Kendrick, Tony; Stuart, Beth; Leydon, Geraldine M; Geraghty, Adam W A; Yao, Lily; Ryves, Rachel; Williams, Samantha; Zhu, Shihua; Dowrick, Christopher; Lewis, Glyn; Moore, Michael
Abstract : Objectives: To determine the feasibility of a trial of patient-reported outcome measures (PROMs) for monitoring primary care patients with depression. Design: Partly individually randomised, partly cluster-randomised controlled trial. Setting: Nine general practices in Southern England. Participants: 47 adults with new episodes of depression: 22 intervention, 25 control. Randomisation: Remote computerised sequence generation and allocation. Interventions: Patient Health Questionnaire, Distress Thermometer Analogue Scale and PSYCHLOPS problem profile for monitoring depression, following diagnosis and at 10–35 days later. Feedback of scores to patients was determined by practitioners. Blinding: Non-blinded, using self-completed measures. Primary outcome: Beck Depression Inventory (BDI-II). Secondary outcome measures: Work and Social Adjustment Scale (WSAS), EuroQol Five-item, Five-level (EQ-5D-5L) Scale for quality of life, modified Client Service Receipt Inventory for costs, Medical Informant Satisfaction Scale (MISS), qualitative interviews with 14 patients and 13 practice staff about feasibility and acceptability of trial design. Results: Three practices failed to recruit the target of six patients in 12 months. Follow-up rates were intervention patients: 18 (82%) at 12 weeks and 15 (68%) at 26 weeks; controls: 18 (72%) and 15 (60%), respectively. At 12 weeks, mean BDI-II score was lower among intervention group patients than controls by 5.8 points (95% CI −11.1 to −0.5), adjusted for baseline differences and clustering. WSAS scores were not significantly different. At 26 weeks, there were no significant differences in symptoms, social functioning, quality of life or costs, but mean satisfaction score was higher among controls by 22.0 points (95% CI −40.7 to −3.29). Intervention patients liked completing PROMs, but were disappointed when practitioners did not use the results to inform management. Conclusions: PROMs may improve depression outcome in the short term, even if PROM scores do not inform practitioners' management. Challenges in recruiting and following up patients need addressing for a definitive trial of relatively brief measures which can potentially inform management. https://www.isrctn.com/search?q=97492541 Trial registration number: ISRCTN 97492541 ; Pre-results.